Effect of porous corncob on the removal of HCN in cigarette mainstream smoke - Yipeng Wang; Yunzhen Jia; Xuehui Sun; Peijian Sun; Song Yang; Quanping Yan; Bin Peng; Jizhao Guo; Xiaobing Zhang; Cong Nie (Materials Research Express, 2021)
In order to reduce the hydrogen cyanide (HCN) release in cigarette mainstream smoke, a new type of porous corncob (PCC) material which was different from traditional corncob-based activated carbon was prepared by a two-step chemical reaction of carboxymethylation and cupric ion complexation. Fourier Transformation Infrared Spectroscopy (FTIR) showed that the carboxymethyl group had been introduced onto the corncob, the carboxymethyl content and the cupric ion loading amount were measured. The x-ray photoelectron spectrometer (XPS) results showed that the Cu content on the surface of PCC was much higher than that of the whole material. The scanning electron microscope (SEM) and nitrogen adsorption-desorption results suggested that PCC had a porous structure. With the increase of the amounts of chloroacetic acid and sodium hydroxide in carboxymethylation reaction and the concentration of cupric ion aqueous solution in complexing reaction, the BET surface areas and pore volumes increased, while the most probable pore sizes of PCCs were close to each other. Compared with the control cigarette, the addition of PCC could effectively remove the HCN release in cigarette mainstream smoke, and the highest reduction rates of HCN per total particulate matter (TPM) was 72.4 %.